Financial Regulation as an Adjustment Screw in the Transformation of Global Capital Markets - Kammel, Armin J. (Thammasat Review of Economic and Social Policy, 2015)
Globalization is typically understood as a process embracing complex economic, technological, socio-cultural and political forces which leads to progressive international integration at various levels. However, this increased interaction and interconnectedness experienced some significant drawbacks due to the global financial crisis (GFC). Although theory stresses that globalization stimulates the emergence of global financial markets leading to a significant transformation of global capital markets, the GFC clearly illustrated that the way forward is a bumpy one. Moreover, the substantial regulatory responses to the GFC led to the establishment of a complex new regulatory environment in the areas of banking and securities regulation in particular. Against this background, the contribution of this article intends to analyze this multiple transformation process by providing creative and provocative considerations on how adjustment screws could serve as a role model for future financial regulation.